2014
DOI: 10.1002/iub.1292
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and endothelial dysfunction

Abstract: Prolonged perturbation of the endoplasmic reticulum (ER) leads to ER stress and unfolded protein response (UPR) and contributes to the pathogenesis of various chronic disorders. This review focuses on the role of ER stress and UPR in endothelial cells and the relevance of these processes to vascular diseases. Chronic activation of ER stress and UPR pathways in endothelial cells leads to increased oxidative stress and inflammation, and often results in cell death. Because endothelial cells play a pivotal role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
120
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 49 publications
1
120
0
2
Order By: Relevance
“…A number of experimental studies in cultured endothelial cells and in animal models suggest a role for ER stress in endothelial dysfunction 7. We were interested in whether acute stimulation of ER stress would produce similar effects in a healthy endothelium as the phenotype observed in the endothelium of patients with DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experimental studies in cultured endothelial cells and in animal models suggest a role for ER stress in endothelial dysfunction 7. We were interested in whether acute stimulation of ER stress would produce similar effects in a healthy endothelium as the phenotype observed in the endothelium of patients with DM.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, the endoplasmic reticulum (ER) has emerged as an important regulator of metabolic processes and recently has been implicated in the pathogenesis of endothelial dysfunction 6, 7, 8. The ER is a large, membrane‐enclosed cellular compartment, critical to the physiologic regulation of many cellular processes, including protein folding, lipid biosynthesis and redox homeostasis 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent in vivo study showed that the administration of the antioxidant vitamin C was able to improve both GLP-1 action and hyperglycemia control [5]. On the other hand, in endothelial cells, GLP-1 may counteract the high glucose-induced endoplasmic reticulum (ER) stress [7], which has been implicated in type 2 diabetes (T2D) and endothelial dysfunction [8,9]. Under ER stress, the unfolded protein response (UPR) is activated in order to restore normal ER homeostasis [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in endothelial cells, GLP-1 may counteract the high glucose-induced endoplasmic reticulum (ER) stress [7], which has been implicated in type 2 diabetes (T2D) and endothelial dysfunction [8,9]. Under ER stress, the unfolded protein response (UPR) is activated in order to restore normal ER homeostasis [8]. UPR acts by promoting the inhibition of protein synthesis, the degradation of misfolded proteins and the production of molecular chaperones involved in protein folding [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation